Beyond Martim Moniz: Portuguese Hindu Gujarati merchants in Lisbon - Cachado,Rita (2017)
Portuguese Hindus living in Greater Lisbon are globally considered as virtuous merchants and they hardly escape this stereotype, which is also appended to other South Asian populations living in Lisbon, regardless of its accuracy. Moreover, common sense features the location of these merchants shops circumscribed to Martim Moniz (near the downtown area). Nevertheless, Portuguese Hindu merchants, as well as other South Asian shopkeepers in Lisbon, have shops spread all over the city. In this article, I give a portrait of Portuguese Hindu merchants in Lisbon in a threefold way. One that unravels the different locations of their stores; another that approaches the diversity of their markets; and finally one that will draw on their view about the Portuguese economic crisis and its implications for their businesses. Until recently, Portuguese Hindus professional trajectories were associated with an upward social mobility. Presently, what are their perspectives made of? How does the economic crisis affect their businesses? Do they prefer to migrate again as their families did two or three times before?